2009
DOI: 10.1002/asia.200900020
|View full text |Cite
|
Sign up to set email alerts
|

Methane Sorption and Structural Characterization of the Sorption Sites in Zn2(bdc)2(dabco) by Single Crystal X‐ray Crystallography

Abstract: Sorption isotherms of methane in Zn(2)(bdc)(2)(dabco) are measured up to a pressure of 35 bar in the temperature range between 198-296 K. The methane sorption measurements at 296 K showed an uptake of 137 cm(3) cm(-3) at 35 bar. The enthalpy of methane adsorption for Zn(2)(bdc)(2)(dabco) estimated by the virial equation is 13.6 kJ mol(-1) at zero coverage. X-ray structure analysis of methane-adsorbed Zn(2)(bdc)(2)(dabco) by synchrotron radiation at 90 K revealed that methane molecules occupy three independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…¼ 3:7 Â 10 9 m 2 s À1 , which would indicate a preferential one-dimensional diffusion in channel direction with an anisotropy of g ¼ 3, or for example D k ¼ 2:6 Â 10 9 m 2 s À1 and D ? ¼ 7:8 Â 10 9 m 2 s À1 , which would indicate a preferential twodimensional diffusion with an anisotropy of g ¼ 1 3 .…”
Section: Combining Spectroscopy and Diffusometry In A Nanoporous Crysmentioning
confidence: 99%
See 1 more Smart Citation
“…¼ 3:7 Â 10 9 m 2 s À1 , which would indicate a preferential one-dimensional diffusion in channel direction with an anisotropy of g ¼ 3, or for example D k ¼ 2:6 Â 10 9 m 2 s À1 and D ? ¼ 7:8 Â 10 9 m 2 s À1 , which would indicate a preferential twodimensional diffusion with an anisotropy of g ¼ 1 3 .…”
Section: Combining Spectroscopy and Diffusometry In A Nanoporous Crysmentioning
confidence: 99%
“…Small molecules like alkanes [2,3], alcoholes [4,5] and carbon dioxide [6][7][8] may be adsorbed in the nanochannels after removal of the initial solvents by activation. With respect to study host-guest interaction in this MOF, carbon dioxide is of special interest since the 13 C chemical shift tensor of the CO 2 molecule displays an anisotropy as large as À335 ppm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Arstad et al reported a CO 2 adsorption capacity of 14.8 mol/kg at 25°C and 24 bar for Ni 2 (BDC) 2 (Dabco) [14]. Several groups have reported that Zn 2 (BDC) 2 (Dabco) has a high CH 4 storage capacity [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic modulation of organic ligands (L) leads also to a series of porous isomorphous MOFs Zn 2 (L) 2 (Dabco), with varying size of pores. Recently promising results have been obtained for the application of pillared-layer MOFs in adsorption and storage of gases such as CO 2 and CH 4 [33][34][35][36][37]. Arstad et al reported a CO 2 adsorption capacity of 14.8 mol/kg at 25°C and 24 bar for Ni 2 (BDC) 2 (Dabco) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Design and synthesis of metal-organic frameworks of Zn(II) and Cd(II) are important due to their functionalities in molecular motors, bio-mimicking models, optoelectronic devices, catalytic activity and as anion exchanger. [23][24][25][26] The advantage of using these d 10 systems as a node in such designed synthesis lies in their flexibility in co-ordination geometry. 24,25 Among the bridging ligands 2,4,6-tri(4-pyridyl)-1,3,5-triazine (tpt) has been used efficiently to exploit its tridentate nature to design different type of coordination frameworks.…”
Section: Introductionmentioning
confidence: 99%